2022
DOI: 10.1186/s12889-022-14707-3
|View full text |Cite
|
Sign up to set email alerts
|

What did the pandemic teach us about effective health communication? Unpacking the COVID-19 infodemic

Abstract: Background The spread of unvetted scientific information about COVID-19 presents a significant challenge to public health, adding to the urgency for increased understanding of COVID-19 information-seeking preferences that will allow for the delivery of evidence-based health communication. This study examined factors associated with COVID-19 information-seeking behavior. Methods An online survey was conducted with US adults (N = 1800) to identify ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 70 publications
0
7
0
1
Order By: Relevance
“…19 This challenge is made even more difficult when considering the low levels of trust accorded to institutions by populations who experience disparities. 20…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…19 This challenge is made even more difficult when considering the low levels of trust accorded to institutions by populations who experience disparities. 20…”
Section: Resultsmentioning
confidence: 99%
“…19 This challenge is made even more difficult when considering the low levels of trust accorded to institutions by populations who experience disparities. 20 The message includes both substance (i.e., the topic, such as signs of dementia) and specific creative features involved in design. The selection of the topic typically aligns with the intended outcome or goal of the campaign.…”
Section: Designing Communication Campaignsmentioning
confidence: 99%
“…Secondly, future research should embrace a diverse array of theoretical perspectives to explore additional factors that may influence the longevity and spread of rumors. This could include conducting more nuanced analyses across different media channels and demographic groups [ 62 ]. Additionally, it would be beneficial to consider the individual characteristics of the public along with other socio-cultural elements [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…More respondents had fears related to loss of employment (53%) than their physical (10%) or mental (4%) health.The study highlights the need for context-speci c communication strategies among vulnerable populations. This includes reliable and accessible sources of information, an emphasis on information accuracy and detail, and a holistic and multidimensional approach to awareness and information sharing.Communication strategies needed to be continually evolved to tackle behavior change hesitancy and COVID-19 fatigue [20].Moreover it was realised that health communication for KAP related to COVID-19 needed to be diversi ed and customized based on socioeconomic and demographic characteristics of a community to be successful [21][22][23]. This is evident from studies in low and middle-income countries (LMIC) which showed how context-speci c issues impacted KAP [2,[24][25] including socioeconomic and demographic characteristics like age, gender, education attainment [6,[26][27], area of residence [28], employment status and income [8,29].KAP was considered especially important among vulnerable populations such as urban informal settlements or slums due to the high density of population [2], illiteracy [5], vulnerability to misinformation [10], unequal access to basic necessities such as water and sanitation [30][31], and inadequate public healthcare systems [2].…”
mentioning
confidence: 99%
“…Moreover it was realised that health communication for KAP related to COVID-19 needed to be diversi ed and customized based on socioeconomic and demographic characteristics of a community to be successful [21][22][23]. This is evident from studies in low and middle-income countries (LMIC) which showed how context-speci c issues impacted KAP [2,[24][25] including socioeconomic and demographic characteristics like age, gender, education attainment [6,[26][27], area of residence [28], employment status and income [8,29].…”
mentioning
confidence: 99%